Nearly gone - Cosimano, Elle (Speak, an imprint of Penguin Group (USA) LLC, 2015)
"A math-whiz from a trailer park discovers she's the only student capable of unravelling complex clues left by a serial killer who's systematically getting rid of her classmates"--